2017
DOI: 10.1103/physrevb.95.125404
|View full text |Cite
|
Sign up to set email alerts
|

Radiative heat transfer between metallic gratings using Fourier modal method with adaptive spatial resolution

Abstract: We calculate the radiative heat transfer between two identical metallic one-dimensional lamellar gratings. To this aim we present and exploit a modification to the widely-used Fourier modal method, known as adaptive spatial resolution, based on a stretch of the coordinate associated to the periodicity of the grating. We first show that this technique dramatically improves the rate of convergence when calculating the heat flux, allowing to explore smaller separations. We then present a study of heat flux as a f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 69 publications
0
41
0
Order By: Relevance
“…The results obtained with the FMM have been verified by means of an independent numerical code, in which a modification to the FMM known as Adaptive Spatial Resolution (ASR) has been implemented. This technique, originally introduced to improve the convergence of the method and to overcome the instabilities observed in particular in the case of metallic gratings [52,53], has been recently employed to calculate the radiative heat transfer between two gold gratings [54]. For the physical system studied in this work, it has given results in agreement (within the numerical precision) with the ones of the FMM.…”
Section: Resultsmentioning
confidence: 89%
“…The results obtained with the FMM have been verified by means of an independent numerical code, in which a modification to the FMM known as Adaptive Spatial Resolution (ASR) has been implemented. This technique, originally introduced to improve the convergence of the method and to overcome the instabilities observed in particular in the case of metallic gratings [52,53], has been recently employed to calculate the radiative heat transfer between two gold gratings [54]. For the physical system studied in this work, it has given results in agreement (within the numerical precision) with the ones of the FMM.…”
Section: Resultsmentioning
confidence: 89%
“…In particular, in the infrared where the Planck function is considerable (at typical experimental temperatures, T 1000 K), Φ Born for all of these materials is significantly larger than the corresponding Φ opt and is highly sensitive to material dispersion; as a specific example, the Born bound for Au lies significantly above the upper limits of the plot over the entire range of frequencies shown. By contrast, the logarithmic dependence of Φ opt on ζ p means that it will generally be much less sensitive to changes in material dispersion except near polariton resonances; this is noticeable in the infrared for [16] and doped Si (blue star) [7] surfaces. ΦBorn for Au is several orders of magnitude above the plotted range and thus not shown.…”
Section: Boundmentioning
confidence: 97%
“…Finally, we compare the power spectrum Φ planar × d 2 /A associated with identical planar films [6,12] to the exact and Born bounds in Fig. 3, specifically considering gold (Au), doped silicon (Si), and silicon carbide (SiC) as representative materials, as well as to the largest heat transfer observed in specific nanostructured Au [16] and Si [7] surfaces studied in the past. (We employ Drude dispersions for Au [16] and Si [7], and a phonon polaritonic dispersion for SiC [17].)…”
Section: Boundmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include surface phonon polaritons that can exist at the surface of polar dielectric materials such as SiO 2 and SiC, or surface plasmon polaritons (SPPs) that can be supported between metallic surfaces or structures [13][14][15][16][17]. Recently, it is demonstrated that surface plasmons in graphene can also achieve a similar role to enhance the photon tunneling between two graphene sheets [18].…”
Section: Introductionmentioning
confidence: 99%